”E-commerce Dalam Pandangan Islam dan Hak Asasi Manusia” - Laili Azizah; Hesti Maelanitasari; Ahmad AL-Amin; Hanief Monady (JURNAL ILMIAH NUSANTARA, 2025)
Materialistic business is an act of buying and selling. As long as it is based on applicable rules or regulations, everyone is given unlimited liberty to engage in activities which are beneficial to themselves, others and their environment. It is the goal of this research to comment on the importance of e-commerce, musmslsh and human rights within QS. Al-Baqarah [2]: 275 and QS. An-Nisa [4]: 29 of Islam. This research is library research with qualitative type of study. The data is analyzed with descriptive analysis method. The results show that the use of e-commerce in transactions is acceptable in accordance with QS. An-Nisa [4]: 29 which explains that transactions are acceptable if mutually agreed between buyers and sellers. This is also in line with Adam Smith's free market theory that says that everybody has the right to freedom in selling and buying and trading.